ANALISIS PENDAPATAN DAN TINGKAT KEMISKINAN RUMAH TANGGA PETANI KAKAO DI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Sinta Okpratiwi; Dwi Haryono; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
The purposes of this research are to analyze the income of cocoa farming, the income of cocoa farmer households, the poverty level of cocoa farmer households, the factors affecting the poverty rate of cocoa farmer households.  This research was conducted in Sungai Langka Village, Gedong Tataan Subdistrict Pesawaran Regency.  Respondents were 51 cocoa farmers taken using stratified random sampling method based on land area.  The analytical methods used were farm income analysis, household income analysis, household poverty level analysis, logistic analysis of farming household poverty level.  The results showed that cash income of cocoa farming is Rp8,027,576.78 per ha per year and revenue at total cost Rp Rp4,335,373.38 per ha per year. The household income of cocoa farmers is Rp21,277,833.33 per year.  Based on the World Bank indicator, the number of nonpoor farmers is 52.94 percent and poor farmers is 47.05 percent.  And based on indicator BPS (2016) there are no poor farmers in food poverty, whereas the number of poor farmers in nonfood poverty is 31.37 percent and nonpoor farmers of 68.63 percent. The common poverty line is 21.57 percent of poor farmers and 78.43 percent of non-poor farmers.  The percentage of the poor is 0.21, the poverty intencity index is 0.042, the poverty severity index is 0.00034.  Factors that affect the poverty level is household income.Key words: cocoa, farming income, household income, poverty rate